Accessibility and Update Status of Published Software: Benefits and Missed Opportunities - Huang, Xunhe; Xie, Jieru; Otecko, Newton O.; Peng, Minsheng (Frontiers in Research Metrics and Analytics, 2017)
Online accessibility and continuous updating of software packages is important for their application and resource-sharing. We evaluated the accessibility and update status of 214 software packages published in Molecular Ecology Resources in the past 15 years (2001–2015) and reported the associated benefits and missed opportunities. Original publications describing these software packages have been cited 31,886 times in total, with 19.6% of them being cited more than 100 times. However, 41.6% (89/214) of the source websites provided in the original papers were inaccessible, of which only 29.2% (26/89) had alternative websites. Up to 63.1% (135/214) of the software packages had not been updated since their publication or were inaccessible. A huge disparity in accessibility, 100% (41/41) vs. 63.6% (110/173), was observed between websites deposited in long-term servers vs. academic institution websites, personal homepages, or e-mails, respectively. In addition, software packages that were accessible and updated were significantly more likely to be cited, compared to those that were inaccessible and un-updated. By guaranteeing the accessibility of their published software packages, for instance, by depositing them in long-term servers and keeping the software packages updated, software developers will further resource-sharing and promote reproduction and citation of their software.